Misinterpretation of Youth Freedom of Expression Against Social Ethics Analysis of QS. Al-Hujurat Verse 6 - Muhamad Dimas Pratama; Halimatussa’diyah; Deddy Ilyas (al-Afkar, Journal For Islamic Studies, 2025)
This research aims to analyze teenagers' understanding of freedom of expression in the context of social ethics based on QS. Al-Hujurat verse 6. In addition, this research evaluates the impact of misinterpretation of freedom of expression on adolescent social behavior and how this verse provides guidelines for maintaining communication ethics in society. This research uses a qualitative method with a library research approach and the tahlili method to analyze QS. Al-Hujurat verse 6. Research results show that misinterpretation of freedom of expression among teenagers, especially on social media, can cause the spread of hoaxes, hate speech and slander which results in damage to social ethics and interpersonal relationships. In QS. Al-Hujurat verse 6 emphasizes the importance of the tabayyun principle in filtering information as well as the balance between the right to expression and social responsibility.